2013
DOI: 10.4321/s1578-84232013000200006
|View full text |Cite
|
Sign up to set email alerts
|

Diferencias de personalidad en entrenadores desde el modelo de Costa y McCrae

Abstract: Diferencias de personalidad en entrenadores desde el modelo de Costa y McCrae Personality differences in coaches from the Costa and MacCrae model Diferenças de personalidade dos treinadores através do modelo de Costa e McCrae

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 5 publications
1
11
0
2
Order By: Relevance
“…El criterio de agrupación de los participantes se basa en el empleado en los trabajo de Reche et al 2010y Boix (2016) donde se clasifica a los deportistas con una experiencia deportiva mayor o menor a cinco años. Además, en el presente trabajo se incluye un tercer grupo formado por participantes con una alta experiencia (igual o superior a diez años), criterio de agrupación empleado en el trabajo de García-Naveira y Ruiz-Barquín (2013). Por último, los integrantes de la muestra se ejercitaban cuatro días a la semana, en sesiones de 90 minutos y competían en la primera o segunda división autonómica valenciana.…”
Section: Método Participantesunclassified
“…El criterio de agrupación de los participantes se basa en el empleado en los trabajo de Reche et al 2010y Boix (2016) donde se clasifica a los deportistas con una experiencia deportiva mayor o menor a cinco años. Además, en el presente trabajo se incluye un tercer grupo formado por participantes con una alta experiencia (igual o superior a diez años), criterio de agrupación empleado en el trabajo de García-Naveira y Ruiz-Barquín (2013). Por último, los integrantes de la muestra se ejercitaban cuatro días a la semana, en sesiones de 90 minutos y competían en la primera o segunda división autonómica valenciana.…”
Section: Método Participantesunclassified
“…Early findings suggested that team sport participants consistently scored higher on extroverted sport scales compared to individual sport participants and non-participants, thereby lending credence to the gravity hypothesis (Eagleton et al, 2007). Another significant theory to consider is the "performance hypothesis" posited by García-Naveira and Ruiz-Barquín (2013) (see also García-Naveira and Ruiz-Barquín, 2016;Garcia-Naveira and Ruiz-Barquín, 2020). This hypothesis emphasizes that certain personality traits are intrinsically linked with enhanced sports performance.…”
Section: Introductionmentioning
confidence: 98%
“…Yet, the discussion extends beyond simply determining if personality affects sports participation and performance. It's essential to highlight, as pointed out by multiple authors, including García Naveira (2010), García-Naveira et al (2011), García-Naveira and Ruiz-Barquín (2016), and Piedmont et al (1999), that personality's influence is twofold. On one hand, it can directly affect the sporting action itself, and on the other, it can exert an indirect influence on the surrounding context and actions intimately tied to an individual's sports performance.…”
Section: Introductionmentioning
confidence: 99%
“…In discussing coach personality, the literature has identified certain common traits in successful coaches [22,24,25]. The traits highlighted by these studies are those related to high emotional stability, sociability and social skills, kindness, tenacity, discipline, openness to experience, responsibility, critical professionalism, and creativity.…”
Section: Introductionmentioning
confidence: 99%